2005
DOI: 10.1677/jme.1.01550
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of functional steroid receptors and ligand-induced responses in telomerase-immortalized human endometrial epithelial cells

Abstract: Information on the regulation of steroid hormone receptors and their distinct functions within the human endometrial epithelium is largely unavailable. We have immortalized human primary endometrial epithelial cells (EECs) isolated from a normal proliferative phase endometrium by stably transfecting the catalytic subunit (hTERT) of the human telomerase complex and cultured these hTERT-EECs now for over 350 population doublings. Active hTERT was detected in hTERT-EECs employing the telomerase repeat amplificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 59 publications
2
40
0
Order By: Relevance
“…All hormone concentrations and protocols were chosen based upon hormone receptor expression studies performed in vitro in endometrial epithelial cells (Hombach-Klonisch et al, 2005), and are within the concentration range reported to be found in endometrial tissue (Nussey and Whitehead, 2001). …”
Section: Methodsmentioning
confidence: 99%
“…All hormone concentrations and protocols were chosen based upon hormone receptor expression studies performed in vitro in endometrial epithelial cells (Hombach-Klonisch et al, 2005), and are within the concentration range reported to be found in endometrial tissue (Nussey and Whitehead, 2001). …”
Section: Methodsmentioning
confidence: 99%
“…37,38 All cells were maintained at 37°C in a humidified incubator with 5% CO 2 . For the steroid hormone treatments, 1 million cells were plated per well on a 6-well plate in 10% fetal bovine serum (FBS) media for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Progesterone (P 4 ) induces cell differentiation in the estrogen-primed endometrium during the secretory phase; it also prepares epithelial cells for blastocyst attachment and provokes decidualization in stromal cells (Hombach-Klonisch et al 2005). The concerted action of estrogens and P 4 is of paramount importance for endometrial receptivity to the embryo (Sharkey & Smith 2003).…”
Section: The Role Of Steroid Hormones On Endometrial Maturation/decidmentioning
confidence: 99%
“…Endometrial stromal cells were isolated as described by Hombach-Klonisch et al (2005) with some modifications (Mannelli et al 2014). The purity of the stromal cells from each specimen was confirmed by immunocytochemistry using vimentin staining and flow cytometry as previously described (Mannelli et al 2014).…”
Section: Culture and Decidualization Of Endometrial Stromal Cellsmentioning
confidence: 99%